Urgensi Pengasuhan Di Masa Usia Dini Terhadap Kesehatan Mental Anak Perspektif Mazhab-Mazhab Konseling - Ali, Muhammad (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2023)
A healthy mentality will produce productive humans. However, mental health does not stand alone, there are many factors that influence it, one of which is parenting at an early age. This study aims to explore the views of counseling schools in explaining the importance of parenting in achieving mental health. This research method uses literature review. The results of the study show that the three schools of counseling differ in understanding the terms mentally healthy and mentally disturbed and differ in terms of the causal factors. Even though they differ in several ways, they agree that early childhood care is important to shape their mental health in the next phases of development